Dealing with Russia - Laborie, Léonard (HAL CCSD, 2022)
Compte rendu des rencontres organisées par le Norway-EU Science Diplomacy Network à Tromsø sur le thème des relations scientifiques avec la Russie, dans le contexte de la conférence Arctic Frontiers. At the beginning of May in Tromsø, Norway, 300 km north of the Arctic Circle, the bite of the cold is still felt. The few leafy trees in town have not yet put on leaves, the cracks in the sidewalks and on the road are filled with melting snow. But even more sensitive are the geopolitical tensions: warships regularly pass through the dark waters between the island and the mainland, a drone flies over the port in the white night without darkness or sun, Russian trawlers are no longer welcome… As Berk Vindevogel writes, « The Arctic is heating up, and not only literally ».